Boi-ogi-to (TJ-20), a Kampo Formula, Suppresses the Inflammatory Bone Destruction and the Expression of Cytokines in the Synovia of Ankle Joints of Adjuvant Arthritic Rats. (7th May 2017) - Zhang, Xinwen; Wu, Zhou; Liu, Yicong; Ni, Junjun; Deng, Chunfu; Zhao, Baohong; Nakanishi, Hiroshi; He, Jing; Yan, Xu
Abstract : TJ-20 is a formula consisting of 6 herbs that has been used in the clinical treatment of rheumatoid arthritis (RA) in China and Japan for centuries. However, scientific evidence of the effects of TJ-20 has not been established. In the present study, we focused on the therapeutic effects and investigated the main function of TJ-20 on adjuvant arthritis (AA), an animal model of RA, which was induced with complete Freund's adjuvant (CFA). TJ-20 was administered orally at 600 mg/kg once a day from 0, 7, and 10 days to 8 weeks after the CFA treatment. TJ-20 significantly ameliorated inflammatory progression and bone destruction in AA in a time-dependent manner. Furthermore, TJ-20 significantly reduced the increased changes in a number of macrophages and helper T cells. Moreover, TJ-20 suppressed the expression of TNF- α whereas it augmented the expression of IL-10 and attenuated Th1 cells responses in the synovia of the ankle joint. Therefore, TJ-20 regulated the expression of proinflammatory and anti-inflammatory cytokines in macrophages and Th1/Th2 balance in the synovia of ankle joints in AA rats. These results suggest the positive anti-inflammatory effect of TJ-20 and provide a scientific basis for the clinical use of TJ-20 for RA.